Les espaces verts urbains : étude exploratoire des pratiques et du ressenti des usagers - Nathalie Long; Brice Tonini (VertigO)
Nowadays, vegetation takes large place in the urban fabric of the occidental cities. Natural spaces are wanted by the urban population to support the city and accept it (Emelianoff, 2007; Da Cunha, 2009). The vegetation contribution is undeniable: vegetation generates calm, well-being, a quality of living environment and contributes to reduce several urban problems like air pollution, water pollution, urban heat island,… (Akbari, 2002; Nowak et al., 2006; Matusoka et Kaplan, 2008). If seven out of ten french people opt for a dwelling near an urban park (UNEP, 2008), several reasons explain this wish : relaxation, meeting, recreation or sport activities, … (Sanesi et Chiarello, 2006). From a survey about feeling and practice of users, realized in three urban parks of Nantes and in a sustainable district of Angers, the users want to be separated from the city, to stay in a quiet space or to practice a recreation activity which varies according to age. The park atmosphere (well-kept garden or wild nature) has not a direct influence on the users feeling. These results precise which vegetation is desired in the city to improve the next urban planning.